2010
DOI: 10.1016/j.jana.2009.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Development, Risk, and Resilience of Transgender Youth

Abstract: Transgender youth face unique and complex issues as they confront cultural expectations of gender expression and how these fit with what is natural for them. Striving for balance, learning to cope, questioning, and eventually becoming comfortable with one's gender identity and sexual orientation are of paramount importance for healthy growth and development. Ineffective management of intense challenges over time without adequate social support places youth at risk for a number of unhealthy behaviors, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 33 publications
1
57
0
4
Order By: Relevance
“…Early on in the transitioning process, many transwomen conceal their gender identities or refrain from disclosing a transgender identity in hopes of "passing" and avoiding social rejection (Stieglitz 2010). This process often began in our study with coming out about being "gay," while avoiding reference to gender identity.…”
Section: Broader Societymentioning
confidence: 98%
“…Early on in the transitioning process, many transwomen conceal their gender identities or refrain from disclosing a transgender identity in hopes of "passing" and avoiding social rejection (Stieglitz 2010). This process often began in our study with coming out about being "gay," while avoiding reference to gender identity.…”
Section: Broader Societymentioning
confidence: 98%
“…Research suggests the transitions in self and identity for transgender people occur earlier in life in Asia compared to North America and Europe (Winter, 2009). Studies have shown transgender youth experience substantial victimization (Garofalo, R., Deleon, J., Osmer, E., Doll, M., & Harper, G. W., 2006;Stieglitz, 2010). Research in the U.S. showed verbal abuse and threats started at an average age of 13, physical abuse, including rape, began on average at age 14, and 77% of transgender youth experienced verbal harassment by parents, 48% by brothers or sisters, and 65% by police officers (Garofalo et al, 2006).…”
Section: Vietnammentioning
confidence: 99%
“…It encourages countries to offer comprehensive sexuality education and promotes an anti-discriminatory approach to sexual and gender diversity. Yet gay, lesbian, bisexual, transgender, intersex and queer (GLBTIQ) students are overlooked in sexuality education around the world (Carlson 1992;Moran 2000;Sears 2005;Stieglitz 2010). There exist controversies about their inclusion even in 'progressive' countries such as Australia (Kissane 2009;Marr 2011).…”
mentioning
confidence: 99%